2000
DOI: 10.2174/1381612003400470
|View full text |Cite
|
Sign up to set email alerts
|

New Synthetic Vitamin D Analogs with Antiproliferative Activities

Abstract: The introduction of oxygen atoms into different positions of the vitamin D side chain is described. By combining the arising 23-oxa and 25-oxa elements with other structural modifications (19-nor, iso-19-nor, 20-methyl, 20-ene, 20,21-cyclo) calcitriol analogs with remarkable levels of dissociation between beneficial acitivities on cell growth regulation and undesired hypercalcemia were identified. Structure-activity relations are elaborated in a very systematic outline of the Schering drug finding program in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…As pointed out previously ZK156979 is characterized by an altered side chain consisting of a 22,23-double bond and a 25-oxa modification. These modifications result in a minute reduction of receptor affinity and 100-fold lower hypercalcemic activity compared with the parent compound calcitriol (Steinmeyer et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As pointed out previously ZK156979 is characterized by an altered side chain consisting of a 22,23-double bond and a 25-oxa modification. These modifications result in a minute reduction of receptor affinity and 100-fold lower hypercalcemic activity compared with the parent compound calcitriol (Steinmeyer et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Antigen-presenting cells as well as T cells have been indicated to function as direct targets of calcitriol, leading to the inhibition of pathogenic effector T helper type 1 (Th1) cytokines as demonstrated in the prevention of Th1-mediated disease-models, whereas the Th2 compartment is not affected or even augmented, and T cells with regulatory properties are also induced, mainly via the promotion of tolerogenic dendritic cells (DCs) . To translate the immunosuppressive capacities of calcitriol into effective immunointervention, great efforts have been put into the design of structural analogs of calcitriol that are devoid of adverse effects on calcium levels due to reduced calcemic activity (Steinmeyer et al, 2000;Mathieu and Adorini, 2002;Zugel et al, 2002;Griffin et al, 2003). The investigation of the 25-oxa series generated a large number of calcitriol analogs exhibiting substantial dissociation between possible immunomodulatory capacities and undesired hypercalcemia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One of these new synthetic vitamin D analogues is ZK156979, being characterized by an altered side chain structure exhibiting the 22‐ene‐25‐oxa modification (Fig. 1) [31,32]. In vivo experiments performed in rats showed for ZK156979 a 100‐fold lower hypercalcemic activity compared with 1,25(OH) 2 D 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The most noteworthy oxa analog of the natural hormone 1α,25-dihydroxyvitamin D 3 (calcitriol, 1 ) is the Chugai Pharmaceutical Company's maxacalcitol ( 2 ); this 22-oxa-25-OH analog is currently a clinically used drug for systemic chemotherapy of secondary hyperparathyroidism and is a drug candidate for topical chemotherapy of psoriasis, an intractable skin disease. Some 23-oxa-25-hydroxy analogs of the natural hormone 1 have been studied, but none surpasses or even matches Chugai's drug, 22-oxa-25-hydroxy 2 , in terms of favorable separation of antiproliferative and prodifferentiation activity from unfavorable calcemic activity . For example, in a broad study of structure−activity relationships (SAR) in 23-oxa-25-hydroxy analogs of 1 , the Schering Corporation found that the potential therapeutic window between desirably high antiproliferative or prodifferentiation activity and desirably low calcemic activity was small for 23-oxa calcitriol, 20-ene-23-oxa calcitriol, and 22-ene-25-oxa calcitriol, compared to a big therapeutic window for the Chugai drug, 22-oxa-25-hydroxy 2 .…”
Section: Introductionmentioning
confidence: 99%